16S/23S rRNA Intergenic Spacer Regions for Phylogenetic Analysis, Identification, and Subtyping of Bartonella Species - Houpikian, Pierre (American Society for Microbiology, 2001)
Species of the genus Bartonella are currently recognized in growing numbers and are involved in an increasing variety of human diseases, mainly trench fever, Carrion's disease, bacillary angiomatosis, endocarditis, cat scratch disease, neuroretinitis, and asymptomatic bacteremia. Such a wide spectrum of infections makes it necessary to develop species and strain identification tools in order to perform phylogenetic and epidemiological studies. The 16S/23S rRNA intergenic spacer region (ITS) was sequenced for four previously untested species, B. vinsonii subsp. arupensis, B. tribocorum, B. alsatica, and B. koehlerae, as well as for 28 human isolates of B. quintana (most of them from French homeless people), six human or cat isolates of B. henselae, five cat isolates of B. clarridgeiae, and four human isolates of B. bacilliformis. Phylogenetic trees inferred from full ITS sequences of the 14 recognized Bartonella species using parsimony and distance methods revealed high statistical support, as bootstrap values were higher than those observed with other tested genes. Five well-supported lineages were identified within the genus and the proposed phylogenetic organization was consistent with that resulting from protein-encoding gene sequence comparisons. The ITS-derived phylogeny appears, therefore, to be a useful tool for investigating the evolutionary relationships of Bartonella species and to identify Bartonella species. Further, partial ITS amplification and sequencing offers a sensitive means of intraspecies differentiation of B. henselae, B. clarridgeiae, and B. bacilliformis isolates, as each strain had a specific sequence. The usefulness of this approach in epidemiological investigations should be highlighted. Among B. quintana strains, however, the genetic heterogenity was low, as only three ITS genotypes were identified. It was nevertheless sufficient to show that the B. quintana population infecting homeless people in France was not clonal.